Does EMS Perceived Anatomic Injury Predict Trauma Center Need?. (1st July 2013) - Lerner, E. Brooke; Roberts, Jennifer; Guse, Clare E.; Shah, Manish N.; Swor, Robert; Cushman, Jeremy T.; Blatt, Alan; Jurkovich, Gregory J.; Brasel, Karen
Abstract Objective. Our objective was to determine the predictive value of the anatomic step of the 2011 Field Triage Decision Scheme for identifying trauma center need. Methods. Emergency medical services (EMS) providers caring for injured adults transported to regional trauma centers in three midsized communities were interviewed over two years. Patients were included, regardless of injury severity, if they were at least 18 years old and were transported by EMS with a mechanism of injury that was an assault, motor vehicle or motorcycle crash, fall, or pedestrian or bicyclist struck. The interview was conducted upon emergency department (ED) arrival and collected physiologic condition and anatomic injury data. Patients who met the physiologic criteria were excluded. Trauma center need was defined as nonorthopedic surgery within 24 hours, intensive care unit admission, or death prior to hospital discharge. Data were analyzed by calculating descriptive statistics, including positive likelihood ratios (+LRs) with 95% confidence intervals (CIs). Results. A total of 11, 892 interviews were conducted. One was excluded because of missing outcome data and 1, 274 were excluded because they met the physiologic step. EMS providers identified 1, 167 cases that met the anatomic criteria, of which 307 (26%) needed the resources of a trauma center (38% sensitivity, 91% specificity, +LR 4.4; CI: 3.9–4.9). Criteria with a +LR ≥5 were flail chest (9.0; CI: 4.1–19.4), paralysis (6.8; CI: 4.2–11.2), two or more long-bone fractures (6.3; CI: 4.5–8.9), and amputation (6.1; CI: 1.5–24.4). Criteria with a +LR >2 and <5 were penetrating injury (4.8; CI: 4.2–5.6) and skull fracture (4.8; CI: 3.0–7.7). Only pelvic fracture (1.9; CI: 1.3–2.9) had a +LR less than 2. Conclusions. The anatomic step of the Field Triage Guidelines as determined by EMS providers is a reasonable tool for determining trauma center need. Use of EMS perceived pelvic fracture as an indicator for trauma center need should be reevaluated. Key words: wounds and injury; triage; emergency medical services; emergency medical technicians